NUMERICAL SIMULATION OF AEOLIAN SALTATION WITHIN THE SEDIMENT TRANSPORT LAYER USING GRANULAR KINETIC THEORY / Simulacion numerica de la saltacion aerea dentro de la capa de transpoprte de sedimentos usando teoria cinetoca granular - MARVAL LUGO, JUAN PEDRO; ROJAS-SOLORZANO, LUIS; CURTIS, JENNIFER (Revista de la Facultad de Ingeniería UCV, 2013)
Most granular flows at environmental conditions are unsteady and exhibit a complex physical behavior. Dune formationand migration in the desert are controlled not only by the flow of saltating particles over the sand bed, but also byturbulent atmospheric airflow. In fact, sediments are transported by the atmospheric airflow within a thin layer only a fewcentimeters above the sandy surface. These jumping particles reach a maximum sediment mass flux level at a certain delaytime (known as the “saturation time”) after the initial movement by sliding and rolling begins. Unlike sediment transportin water where the particles are lifted by the turbulent suspension, the saltating particles are kept alive in the layer mainlydue to particle-particle and particle-bed collisions. In order to model this Aeolian transport of sand, Jenkins and Pasini(2005) proposed a two-fluid model (one-dimensional and steady state) using Granular Kinetic Theory (GKT) to describethe solid-phase stress. The present work extends the original idea of Jenkins and Pasini by using a more robust model ofGKT for the kinetic/collisional contributions to the solid-phase stress tensor, together with a friction model for sustainedcontacts between particles. In addition, a standard k-ε turbulence model for the air and a drag model for the interactionbetween the phases is employed. A rectangular 2D geometry was chosen with a typical logarithmic profile for the inlet airvelocity, along with an initial amount of sand at rest in the lower part of the simulation domain, resembling the particlesaltating flow commonly seen in the vertical middle plane within Saltation wind tunnels. This model is validated withexperimental data from Liu and Dong (2004) and the results given by Pasini and Jenkins (2005) and Marval et al. (2007).A good estimation for the particle erosion and mass flux in the Saltation layer is predicted, even though the profiles of massflux and concentration within the transport layer are very thin and close to the bed. RESUMEN La mayoría de los flujos granulares que ocurren en condiciones ambientales son inestables y exhiben un complejocomportamiento físico. La formación y migración de dunas en los desiertos son controladas no sólo por el flujo departículas en saltación sobre el lecho arenoso, sino también por el flujo turbulento de aire atmosférico. Estas partículas ensaltación alcanzan un flujo másico de sedimentación máximo luego de cierto tiempo luego de la movilización inicial pordesplazamiento y rodamiento. A diferencia del transporte de sedimentos en agua, en el cual las partículas son elevadas porla suspensión turbulenta, las partículas en saltación son avivadas en la capa principalmente por los choques existentes departícula-partícula y partícula-lecho arenoso. Para el modelado de la teoría de Transporte Eólico de Arena, Jenkins y Pasini(2005) propusieron un modelo bifásico (un estado estable y unidimensional) usando la Teoría Cinética Granular (TCG)para describir los esfuerzos en la fase sólida. El presente trabajo extiende la idea original de Jenkins y Pasini usando unmodelo más robusto de TCG para las contribuciones cinéticas/colisionales a los esfuerzos tensores de la fase sólida, juntoa un modelo de fricción para los contactos continuos entre partículas. Fue seleccionada una geometría 2D rectangular conun perfil logarítmico típico para la velocidad de entrada del aire. Este modelo es validado con datos experimentales de Liuy Dong (2004) y los resultados dados por Pansini y Jenkins (2005) y Marval (2007). Una buena estimación para la erosiónde las partículas y el flujo másico de saltación es predicha.Palabras Clave: Saltation layer, Granular kinetic theory, CFD